Rapid Synthesis of N‐Tosylhydrazones under Solvent‐Free Conditions and Their Potential Application Against Human Triple‐Negative Breast Cancer. Issue 12 (21st November 2018) - Xie, Zengyang; Song, Yuying; Xu, Lujia; Guo, Yukun; Zhang, Min; Li, Limei; Chen, Kai; Liu, Xue
Abstract: Some N ‐tosylhydrazone derivatives were effectively synthesized under solvent‐free conditions by using a grinding method at room temperature. The short reaction time, clean and mild process with simple workup and easy purification of the target compounds were salient features of the present protocol, which enables straightforward access to N ‐tosylhydrazones. Among the tosylhydrazone derivatives evaluated, compound3 l exhibits excellent apoptosis‐promoting and anticancer potential against triple‐negative breast cancer (TNBC) cell lines. This research shows that our synthesized compound3 l may be a desirable and effective therapeutic drug against TNBC. Abstract : Daily grind : Some N ‐tosylhydrazone derivatives are effectively synthesized under solvent‐free conditions by using a grinding method. The short reaction time, clean and mild process with simple workup and easy purification of target compounds are salient features of the protocol, which enables straightforward access to N ‐tosylhydrazones. Among the tosylhydrazone derivatives evaluated, one compound exhibits excellent apoptosis‐promoting and anticancer potential against triple‐negative breast cancer (TNBC) cell lines, indicating that our synthesized compound may be a desirable and effective therapeutic drug for TNBC.